Teacher training, family support, self-efficacy, and achievement motivation a case study of madrasah tsanawiyah Negeri Lubuk Pakam, Deli Serdang, North Sumatera, Indonesia - Khairunnisak Khairunnisak; Muafi Muafi (Universitas 'Aisyiyah Yogyakarta, 2019)
This study discusses how teacher training, family support and self efficacy have an effect on achievement at motivation of Madrasah Tsanawiyah Lubuk Pakam, Deli Serdang, North Sumatera, Indonesia. The purpose of this study was to examine and analyze the effect of teacher training with the role of self efficacy as mediation on chievement motivation and influence of family support to motivation achievement teacher of State at Madrasah Tsanawiyah of Lubuk Pakam, Deli Serdang, North Sumatera, Indonesia The sampling technique used a census technique with 43 respondents teacher of State at Madrasah Tsanawiyah Negeri Lubuk Pakam, Deli Serdang, North Sumatra, Indonesia and have attended teacher certification training. The analytical tool used is SmartPLS v.3.2.7 with SEM (Structural Equation Modeling) analysis method. Finally, results revealed a positive and significant effect on selfefficacy, self-efficacy a positive and significant effect on achievement motivation, family support a positive and significant impact on achievement motivation, self-efficacy proven to mediate the influence of teacher training on achievement motivation.